Pierre and His People: Tales of the Far North. Complete - Parker, Gilbert, 1862-1932 (Salt Lake City, UT : Project Gutenberg, 2004)
"Pierre and His People: Tales of the Far North" by Gilbert Parker is a collection of short stories that reflects on life in the Canadian wilderness, likely written in the late 19th century. The narratives focus on the character of Pierre, a French half-breed, and his interactions with the diverse people and landscapes of the Far North, capturing both the beauty and brutality of frontier life. The opening of the book introduces the intricate relationships and social dynamics within a remote community. It features characters like Pretty Pierre, who blends charm with a calculating nature, and Sergeant Fones, whose strictness and adherence to duty set him at odds with the local inhabitants. The dialogue-driven scenes depict tense interactions revolving around law enforcement, personal loyalties, and the enduring challenges of survival against nature and societal pressures. The themes of fate, morality, and the complexity of human relationships begin to emerge as these characters grapple with their identities and responsibilities in a harsh and unforgiving landscape. (This is an automatically generated summary.)
The patrol of the Cypress Hills -- God's garrison -- A hazard of the North -- A prairie vagabond -- She of the Triple Chevron -- Three outlaws -- Shon McGann's tobogan ride -- Père Champagne -- The Scarlet Hunter -- The stone -- The tall master -- The crimson flag -- The flood -- In Pipi Valley -- Antoine and Angelique -- The cipher -- A tragedy of nobodies -- A sanctuary of the plains.
Release date is 2004-11-16
Produced by David Widger
Keywords: Canada, Northern -- Fiction; Short stories, Canadian